i just realised i made a silly mistake way earlier on sorry!
hi this is part of a question I was doing which wasn't really difficult, but i had a question about a section where I didn't get the same part using 2 methods...
I have to show: m-n = (p-q)^3
and the equations are: 2p^3 - 3(p+q)p + 6qp^2 = m
and 2q^3 - 3pq - 3q^2 + 6pq^2 = n
so if u simply subtract the 2 equations, you get the answer.. but i don't get it when i form 2 equations with:
-3pq= ..... for both, and then equating their left sides